The Error-Prone Kinetochore-Microtubule Attachments During Meiosis I in Vitrified Oocytes - Gao, Lei; Hou, Yunpeng; Zeng, Shenming; Li, Junyou; Zhu, Shien; Fu, Xiangwei (Frontiers in Cell and Developmental Biology, 2020)
Oocytes vitrification is frequently applied in assisted reproductive technologies. However, chromosomes segregation was error-prone during meiosis maturation of vitrified oocytes. The fidelity of chromosomes segregation depends on the correct kinetochore-microtubule attachments (KT-MTs). In meiosis I, the Aurora B/C would not spatially separate from the attachment sites upon bivalents stretched. Oocytes lack a mechanism for coordinating bivalent stretching and Aurora B/C inhibition in meiosis I. Thus, the KT-MTs are unstable in oocytes. In this study, we firstly found the incorrect KT-MTs were markedly increased in vitrified oocytes. The Aurora B/C activity in vitrified oocytes was significantly increased when the bivalents were stretched. This Aurora B/C activity could not induce a SAC response, as the SAC protein Mad2 was significantly decreased during MI stage in vitrified oocytes. Thus, the KT-MTs in vitrified oocytes were error-prone. This study, for the first time, revealed the mechanism of the incorrect KT-MTs occurred in vitrified oocytes and provided a theoretical basis for further improvement of oocytes vitrification.